Quelle forêt pour la transition territoriale ? - Simon Lacourt (Projets de Paysage)
The way the organization of a territory evolves is intimately related to the gradual separation between the city, agriculture, and the forest. This involves a succession of territorial transitions that take place in distinct stages and which are characterised by social, geographical, and political changes. The specialisation of each component of the landscape erases an original organisation which is of a hybrid and heterogeneous nature and cultural and urbanised landscapes have become simpler and more homogenous. The city and agriculture are either reinventing new forms or seeking innovative solutions in a new territorial organisation, but what about the forest in this territorial transition? Which type of forest is being considered and what are the current notions relating to it on a territorial scale?